2019
DOI: 10.1371/journal.pone.0215155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maerua subcordata (Gilg) DeWolf on electrophile-responsive element (EpRE)-mediated gene expression in vitro

Abstract: Plant extracts and phytochemicals may prevent chronic diseases via activation of adaptive cellular stress response pathways including induction of antioxidant and phase II detoxifying enzymes. The regulatory regions of these inducible genes encode the electrophile-response element (EpRE). This study tested the EpRE induction ability of Maerua subcordata (fruit, leaf, root, seed) methanol extracts and selected candidate constituents thereof, identified by liquid chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Previous reports have shown that quaternary ammonium compounds, including tetramethylammonium (TMA), 3-hydroxyl-1,1-dimethylpyrrolidiniurn, glycinebetaine, proline betaine (stachydrine), proline betaine ethyl ester, 3-hydroxyprolinebetaine (3-hydroxy-stachydrine), choline, and feruloyl choline, were identified in different Maerua spp., including M. subcordata. 38,39 Also, it was shown that acetylcholine, TMA, and related quaternary ammonium compounds acted on muscarinic receptors in the intestinal smooth muscle and that TMA exhibited a biphasic effect. Contractions caused by TMA in the presence of hyoscine have been suggested to be probably due to "rebound contractions".…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that quaternary ammonium compounds, including tetramethylammonium (TMA), 3-hydroxyl-1,1-dimethylpyrrolidiniurn, glycinebetaine, proline betaine (stachydrine), proline betaine ethyl ester, 3-hydroxyprolinebetaine (3-hydroxy-stachydrine), choline, and feruloyl choline, were identified in different Maerua spp., including M. subcordata. 38,39 Also, it was shown that acetylcholine, TMA, and related quaternary ammonium compounds acted on muscarinic receptors in the intestinal smooth muscle and that TMA exhibited a biphasic effect. Contractions caused by TMA in the presence of hyoscine have been suggested to be probably due to "rebound contractions".…”
Section: Discussionmentioning
confidence: 99%